A rapid, high-yield and large-scale synthesis of uniform spherical silver nanoparticles by a microwave-assisted polyol process - Helmlinger, Jens; Heise, Martin; Heggen, Marc; Ruck, Michael; Epple, Matthias (RSC Advances, 2015)
Silver nanoparticles are often employed in medical devices and consumer products due to their antibacterial action. For this, reliable syntheses with quantitative yield are required. Uniform spherical silver nanoparticles with a diameter of about 180 nm were synthesized by carrying out the polyol synthesis in a microwave. Silver nitrate was dissolved in ethylene glycol and poly(N-vinyl pyrrolidone) (PVP) was added as capping agent. The particles were characterized by SEM, HRTEM, XRD, and DLS. The results are compared with the classical method where silver nitrate is reduced by glucose in aqueous solution, heated with an oil-bath. The microwave-assisted synthesis leads to an almost quantitative yield of uniform silver nanoparticles after 20 min reaction time and gives exclusively spherical particles without other shapes like triangles, rods or prisms. Diethylene glycol as solvent gave a more homogeneous particle size distribution than ethylene glycol. For both kinds of particles, dissolution in ultrapure water was examined over a period of 29 days in the presence of oxygen. The dissolution was comparable in both cases (about 50% after 4 weeks), indicating the same antibacterial action for particles from the microwave and from the glucose synthesis.
CRIS-Team Scopus Importer:2023-03-20